Synergistic effect of additives on reducing asphalt binder aging - Iwański, Mateusz Marek; Durlej, Małgorzata; Janus, Karolina (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
As an organic material, asphalt binder undergoes a aging process, the intensity of which depends on the stage of its technological use. The binder is exposed to high temperatures, which cause its oxidation. The viscoelastic properties of the binder deteriorate. Research is being conducted to limit the effects of asphalt aging. One of the directions is individually dosed chemical additives to be used in the binder. In the article, a combination of synthetic wax (SWLC) and tall oil amidopolyamine (TOA) was used for the first time in the binder, in concentrations of 1.0%, 1.5%, 2.0% and 2.5% and in the amounts of 0.0%, 0.2%, 0.4% and 0.6% by weight in relation to asphalt. The function of these additives is to act as aging inhibitors and to improve the basic properties of the binder. The resulting binders containing combinations of SWLC and TOA were then subjected to short-term and long-term aging. The effects of aging on penetration at 25◦C, softening point and dynamic viscosity were analyzed, and their aging indices were determined. The penetration index and plasticity range of the modified asphalt were also determined. A synergistic effect of SWLC and TOA was observed at the recommended amounts of 2.0% and 0.4% relative to the asphalt, which ensured a favorable change in the analyzed binder parameters. The results obtained are therefore of significant importance for road engineering practice in the design and construction of durable and sustainable road pavements and the possibility of using this type of binder in the environmentally friendly Warm Mix Asphalt technology.